The Robustness of Strong Stability of Positive Homogeneous Difference Equations - The Anh Bui; Dang Xuan Thanh Duong (Journal of Applied Mathematics)
We study the robustness of strong stability of the homogeneous difference equation via the concept of strong stability radii: complex, real and positive radii in this paper. We also show that in the case of positive systems, these radii coincide. Finally, a simple example is given.